Broadening and Strengthening Underrepresented Group Inclusion in Immunological Research - Smolock, Elaine; Robert, Jacques (Frontiers in Immunology, 2020)
Promoting diversity across biomedical fields is crucial for building comprehensive and innovative research programs, as well as providing trainees from underrepresented groups (URGs) the ability to establish agency and develop skills in a culturally and structurally supportive environment. Despite this awareness, there is still a lack of students from URGs being trained for independent research careers. The Immunology, Microbiology, and Virology (IMV) graduate program at the University of Rochester School of Medicine and Dentistry (URSMD) has been working for the last 13 years to increase diversity through an NIH funded Post-baccalaureate Research Education Program (PREP). Historically, our program has trained URG scholars in Immunology, but as we have progressed we have embraced the understanding that both the scholars and the institution benefit from expanding the interdisciplinary nature of our program. Over the last 3 years, we have integrated a broader and highly collaborative faculty mentor pool, including representation from Immunology, Microbiology, Virology, Neuroscience, Genetics, Biochemistry, Biophysics, Toxicology, and Biomedical Engineering. This expansion, coupled with changes in our education program, including skill building workshops and cross campus integration with our student diversity groups and the Office of Diversity and Inclusion, has strengthened the competitiveness and success of our cohorts. These improvements are enhancing the diversity of our graduate school, creating a research environment that retains students from URGs in biomedical research. We attribute our success to the interdisciplinary and team-building nature of our pipeline program, as well as the URSMD's initiatives to be a more inclusive and equitable institution.